Evaluasi Pengelolaan Obat Yang Mendekati Waktu Kedaluwarsa Tahun 2024 Di Instalasi Farmasi RS X Ngawi - diah nurcahyani (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
A drug that is nearing its expiration date is a drug that is approaching the expiry date determined by the manufacturer, where the expiry date of a drug is determined by counting from the production date to the last test results which show that the drug still meets the criteria for stable drug quality for use by patients. This study aims to find out the results of an evaluation of drug management with a time approaching expiration in 2024 at the X Ngawi Hospital Pharmacy Installation. This research used a descriptive method by collected data retrospectively by observed and evaluated drug evaluation data which is approaching its expiration date in 2024. From the results of a sample study of 60 types of drugs, it is known that 28.30% of drugs can be used or as many as 17 types of drugs, drugs that can be used. 66.70% were returned or 40 types of drugs, and 5.00% were expired or destroyed or 3 types of drugs out of a total of 1220 types of drugs